Corporate Social Responsibility and Firm Productivity: Evidence from the Chemical Industry in the United States - Sun, Li; Stuebs, Marty (2013)
Prior research suggests that participating in corporate social responsibility (CSR) activities can lead to higher future productivity. However, the empirical evidence is still scarce. The purpose of this study is to examine the relationship between CSR and future firm productivity in the U.S. chemical industry. Specifically, this study examines the relationship between CSR in year t and firm productivity in year (t + 1), (t + 2), and (t + 3). We use Data Envelopment Analysis, a non-parametric method, to measure firm productivity. Results from the regression analysis support a significantly positive relationship between CSR and future firm productivity, suggesting that CSR can lead to higher productivity in the chemical industry. The findings add to the validity of the proposition in prior research.
Keywords: Chemical Industry; Firm productivity; Corporate Social Responsibility